Development of Micro Teaching-Learning Model Based on YouTube Channel in Distance Learning to Improve Students’ Basic Teaching Ability - Ajat Sudrajat; Ojat Darojat; Dudung Amir Soleh; Lisa Dwi Ningtyas (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2022)
AbstractTeacher students who have taken the micro-teaching course are expected to master eight essential teaching competencies, namely: 1) opening and closing learning skills, 2) explaining skills, 3) questioning skills (basic, advanced), 4) variation skills, and 5) reinforcement skills, 6) class management skills, 7) small group and individual learning skills, 8) skills to lead small group discussions. YouTube-based microteaching-learning is expected to help master the eight essential competencies even in online learning conditions such as in the Terbuka University. This research was R & D using two classes with 50 students for the control classand 50 students for the treatment class. . From the results obtained in this study, the YouTube channel learning video product is proven effective in improving students' teaching abilities in microteaching courses. Hence, it is recommended for lecturers or teachers at schools to be able to complete their learning media by using videos that are integrated with YouTube to maximize the improvement of students' abilities. AbstrakSiswa guru yang telah mengikuti mata kuliah micro teaching diharapkan menguasai 8 kompetensi dasar mengajar, yaitu: 1) keterampilan membuka dan menutup pembelajaran, 2) keterampilan menjelaskan, 3) keterampilan menanya (dasar, lanjutan), 4) keterampilan variasi, 5 ) keterampilan memberi. penguatan, 6) keterampilan mengelola kelas, 7) keterampilan belajar kelompok kecil dan individu, 8) keterampilan memimpin diskusi kelompok kecil. Pembelajaran mikro berbasis YouTube ini diharapkan dapat membantu penguasaan 8 kompetensi dasar bahkan dalam kondisi pembelajaran online seperti di Universitas Terbuka. Jenis penelitian ini adalah R&D menggunakan 2 kelas, 50 siswa masuk kelas kontrol dan 50 siswa masuk kelas perlakuan. Hasil yang didapat dari penelitian ini. Produk video pembelajaran channel youtube terbukti efektif dalam meningkatkan kemampuan mengajar siswa pada mata kuliah microteaching. Disarankan kepada dosen atau guru di sekolah untuk dapat melengkapi media pembelajarannya dengan menggunakan video yang terintegrasi dengan youtube untuk memaksimalkan peningkatan kemampuan siswa.How to Cite: Sudrajat, A., Darojat, O., Soleh, D. A., Ningtyas, L. D. (2022). Development of Micro Teaching-Learning Model Based on YouTube Channel in Distance Learning to Improve Students’ Basic Teaching Ability. TARBIYA: Journal of Education in Muslim Society, 9(2), 51-62. doi:10.15408/tjems.v9i1. 25512.